2019
DOI: 10.1111/jcap.12244
|View full text |Cite
|
Sign up to set email alerts
|

Virtual behaviors affecting adolescent mental health: The usage of Internet and mobile phone and cyberbullying

Abstract: Problem An important environmental factor affecting adolescents today is undoubtedly technological tools. This descriptive and cross‐sectional study was conducted to evaluate the relationship of adolescents’ Internet and mobile phone usage, cyberbullying behaviors, and their self‐reported mental health. Methods The sample of the study consisted of a total of 426 students including 215 male students and 211 female students. A questionnaire was prepared by the researcher to determine the sociodemographic and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 65 publications
3
24
0
1
Order By: Relevance
“…Anonymity and confidentiality were assured. The questionnaire took the participants about 30 minutes ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…Anonymity and confidentiality were assured. The questionnaire took the participants about 30 minutes ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…For the cross-sectional studies, findings were consistently reported as null in 2/12 studies [ 71 , 117 ], while more sedentary behaviour was favourable in 1/12 studies [ 118 ], unfavourable in 1/12 studies [ 119 ], and mixed findings were reported for 8/12 studies [ 39 , 63 , 65 , 68 , 120 123 ]. No consistent findings were reported across exposure categories.…”
Section: Resultsmentioning
confidence: 99%
“…However, consistent findings in some studies were observed as null for homework [ 117 ], and sedentary time [ 71 ]. More homework was favourable for social-emotional indicators [ 118 ] and unfavourable for social-emotional indicators [ 119 ]. Overall, the quality of evidence was rated as very low due to serious risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Existing findings suggest a significant positive correlation between mobile phone addiction and depression ( Çağan et al, 2014 ; Xiaodan et al, 2016 ; Alhassan et al, 2018 ). Teenagers who spend longer on social media with mobile phones score higher on the depression scale on average ( Calpbinici and Tas Arslan, 2019 ), and retrospective studies have also shown that mobile phone addiction can lead to depression, anxiety, and sleep problems ( Thomee, 2018 ).…”
Section: Introductionmentioning
confidence: 99%